Cognitive Usability Evaluation of Electronic Health Record Systems (CUE-E). Issue 1 (September 2019) - Pfaff, Mark S.; Anganes, Amanda; Eris, Ozgur; Prior, Aileen; Ward, Merry; Nebeker, Jonathan
This project's purpose was to develop cognitively-focused usability evaluation methods for electronic health records (EHRs). This research involved developing a conceptual framework for evaluating EHR usability in terms of clinical cognition and operationalizing the framework in the form of two novel EHR usability evaluation methods. The two evaluation methods - one observational and one lab-based - are described in a suite of protocol materials and recommendations for EHR evaluation and design. This resulting body of work is referred to as CUE-E: Cognitive Usability Evaluation - EHR. This paper describes the process behind the development of the CUE-E evaluation methods, summarizes the use of both, and discusses directions for future work. The two CUE-E evaluation methods are currently ready for pilot applications to assess their reliability and validity and identify opportunities for further improvement.